Effect of the particle size on the performance of BaTiO3 piezoelectric ceramics produced by additive manufacturing. Issue 1 (1st January 2022) - Chen, Xiaoteng; Sun, Jinxing; Guo, Binbin; Wang, Yue; Yu, Shixiang; Wang, Wei; Bai, Jiaming
Abstract: The fabrication of barium titanate (BaTiO3 ) lead-free piezoelectric ceramics using additive manufacturing technology, especially digital light processing (DLP), has been gaining a growing interest for electrical applications. The particle size of the ceramic powders plays a key factor on the performance of sintered ceramic components. In this paper, BaTiO3 ceramic components were fabricated by adopting different suspensions filled with the submicron powder particle size of 200 nm, 500 nm and 600 nm, respectively. Subsequently, the effects of particle size on the rheological properties and photopolymerization behaviors of the suspensions, as well as the density, grain size, piezoelectric and dielectric properties of the ceramic components, were investigated. The result indicated that the suspensions with the coarsest powder showed the lowest viscosity and the highest cure depth; when the grain size distributed in submicron range, the piezoelectric constant ( d 33 ) and relative permittivity ( ε r ) of sintered BaTiO3 ceramic are direct positively correlated to the grain size. The value of ε r and d 33 were related with domain structure affected by grain size. This work can provide a potential valuable guidance for researchers in selecting suitable BaTiO3 powders to obtain high-performance piezoelectric ceramic components when using the DLP process.